Find the value of a and b so that x^3-10x^2+ax+b is exactly divisible by x-1 as well as x-2
Answers
Answered by
4
Hello,
Since, there are two variables , we will get two equations from which we can solve the problem.
Now,
P(x) = x³-10x²+ax+b
The polynomial is divisible by x-1
So ,
By remainder theorem
P(1) =0
So , putting the values :-
P(1) = 1³-10*1²+a+b
Or ,
1-10+a+b = 0
a+b = 9..........(1)
Also ,
Polynomial is divisible by x-2
So ,again by remainder theorem
P(2) =0
So,
2³-10*2²+2a+b =0
8-40 +2a +b =0
2a +b = 32..........(2)
Now ,
Subtracting 1 from 2.
We get
2a +b - (a+b) =32-9
2a + b - a-b = 23
a = 23
Putting the value of a in equation 1 to obtain b
a+b =9
b = 9 - a = 9-23 = (-14)
Hope this will be helping you......
Since, there are two variables , we will get two equations from which we can solve the problem.
Now,
P(x) = x³-10x²+ax+b
The polynomial is divisible by x-1
So ,
By remainder theorem
P(1) =0
So , putting the values :-
P(1) = 1³-10*1²+a+b
Or ,
1-10+a+b = 0
a+b = 9..........(1)
Also ,
Polynomial is divisible by x-2
So ,again by remainder theorem
P(2) =0
So,
2³-10*2²+2a+b =0
8-40 +2a +b =0
2a +b = 32..........(2)
Now ,
Subtracting 1 from 2.
We get
2a +b - (a+b) =32-9
2a + b - a-b = 23
a = 23
Putting the value of a in equation 1 to obtain b
a+b =9
b = 9 - a = 9-23 = (-14)
Hope this will be helping you......
Answered by
1
x - 1 and x -2 are factors of x³ - 10x² + ax +b
So f(x) = x - 1
x - 1 = 0
x = 1
x³ - 10x² + ax + b = 0
(1)³ - 10(1)² + a(1) + b =0
1 - 10 + a + b = 0
a + b = 9 (Equation 1)
f(x) = x - 2
x - 2 = 0
x = 2
x³ - 10x² + ax + b =0
(2)³ - 10(2)² + a(2) + b = 0
8 - 40 + 2a + b = 0
2a + b - 32 = 0
2a + b = 32 (Equation 2)
Subtracting equation 2 from 1
a + b =9
- 2a - b = - 32
- a = - 23
a = 23
23 + b = 9
b = - 14
The values of a and b are 23 and -14
Hope this helps you.
So f(x) = x - 1
x - 1 = 0
x = 1
x³ - 10x² + ax + b = 0
(1)³ - 10(1)² + a(1) + b =0
1 - 10 + a + b = 0
a + b = 9 (Equation 1)
f(x) = x - 2
x - 2 = 0
x = 2
x³ - 10x² + ax + b =0
(2)³ - 10(2)² + a(2) + b = 0
8 - 40 + 2a + b = 0
2a + b - 32 = 0
2a + b = 32 (Equation 2)
Subtracting equation 2 from 1
a + b =9
- 2a - b = - 32
- a = - 23
a = 23
23 + b = 9
b = - 14
The values of a and b are 23 and -14
Hope this helps you.
Similar questions